Um índice de governança corporativa para o mercado acionário brasileiro - Thais Alves dos Santos (2018)
The main purpose of this study was to elaborate an index of corporate governance for the companies traded in B3. The sample of this work was constituted by one hundred and sixteen publicly traded, with papers in negotiation or already negotiated in B3. The nature of the study is quantitative, and the construction of the corporate governance index happened through the principal component analysis. The period of analysis of this work is comprised between the years 2010 and 2016. The work sought to identify which corporate governance dimension has greater weight when classifying the companies with respect to their governance. Among the five dimensions, the composition of the board of directors was the one that presented the greatest weight in the composition of the governance index. After elaborated, the index was compared with the companys financial performance variables through regression with panel data. The results pointed to a positive but not significant relationship between the governance index and financial performance variables. The importance of the results found is emphasized since the elaborated index was made after the new rules of accounting presentation start and, thereafter, it contributes to the discussion of corporate governance. Since, even with the new accounting standards, some companies information still not been easy to find.